2019
DOI: 10.3390/brainsci9030064
|View full text |Cite
|
Sign up to set email alerts
|

Local and Relayed Effects of Deep Brain Stimulation of the Pedunculopontine Nucleus

Abstract: Our discovery of low-threshold stimulation-induced locomotion in the pedunculopontine nucleus (PPN) led to the clinical use of deep brain stimulation (DBS) for the treatment of disorders such as Parkinson’s disease (PD) that manifest gait and postural disorders. Three additional major discoveries on the properties of PPN neurons have opened new areas of research for the treatment of motor and arousal disorders. The description of (a) electrical coupling, (b) intrinsic gamma oscillations, and (c) gene regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…The PPN comprises part of the so-called MLR in the brain stem and is the final output of the cortico-subcortical loops that regulate gait initiation and adaptation (Garcia-Rill et al, 2015). More recent studies have suggested that low frequency stimulation (40–60 Hz) effectively activates the PPN, whereas high frequency stimulation (> 80 Hz) inactivates the same structure (Garcia-Rill et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PPN comprises part of the so-called MLR in the brain stem and is the final output of the cortico-subcortical loops that regulate gait initiation and adaptation (Garcia-Rill et al, 2015). More recent studies have suggested that low frequency stimulation (40–60 Hz) effectively activates the PPN, whereas high frequency stimulation (> 80 Hz) inactivates the same structure (Garcia-Rill et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PPN stimulation can reduce FOG in some patients (Moro et al, 2010; Thevathasan et al, 2011). In animal models, rostral PPN neurons are strongly interconnected with the basal ganglia, including the STN and globus pallidus interna (Garcia-Rill et al, 2019). Cortical regions, such as supplementary motor area (SMA), may also be involved (Shine et al, 2013a; Snijders et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced activity of the locus coeruleus (LC) in PTSD may lead to reduced adrenergic inhibition of the PTN that permits an increase in anxiety, hyperarousal, and drive for rapid eye movement (REM) sleep with nightmares and traumatic memories (flashbacks). The PTN also participates in the regulation of posture and locomotion, gait instability, falling, and voluntary movement [ 123 ].…”
Section: Pedunculotegmental Nuclei (Ptn) Pontis Oralis (Po) and Acety...mentioning
confidence: 99%
“…It is capable of influencing and regulating all levels of basal ganglia and corticostriatal activity other than being a vital component of brainstem reticular and motor control circuitry. Besides this, PPTg has served as a pivotal target area for DBS for the treatment of several neurodegenerative disorders [11]. The PPTg primarily consists of a subpopulation of coleogenic, glutamergic, and GABAergic neurons in the brain stem [12], and it has been mainly involved in hippocampus formation and theta rhythm.…”
Section: Introductionmentioning
confidence: 99%